Comparison of demographic, clinical and laboratory characteristics between first and second COVID-19 waves in a secondary care hospital in Qatar: a retrospective study - Prem Chandra; Vamanjore A Naushad; Nishan K Purayil; Abazar Ahmad M Saeed; Pradeep Radhakrishnan; Irfan Varikkodan; Joe V Mathew; Jaseem Sirajudeen; Riyadh A Hammamy; Ahmad M Badi; Aasir M Suliman; Mohamed N Badawi; et al. (BMJ Open, 2022)
Objective To compare the patient profile and outcomes in Qatar during the first and second waves of the COVID-19 pandemic.Setting A retrospective observational study was conducted comparing the demographic, clinical and laboratory characteristics of patients with COVID-19 infection admitted to a secondary care hospital, during the first and second waves of the pandemic.Participants 1039 patients from the first wave and 991 from the second wave who had pneumonia on chest X-ray and had a confirmed SARS-CoV-2 infection by a real-time PCR test of a nasopharyngeal swab were included. Patients with a normal chest X-ray and those who had a negative PCR test despite a positive COVID-19 antigen test were excluded.Outcome Length of stay, need for mechanical ventilation, final disposition and mortality were the key outcomes studiedResults Influenza like symptoms (18.5% in the first wave vs 36.1% in the second wave, p 0.001), cough (79.2% vs 87%, p<0.001) and dyspnoea (27.5% vs 38% p<0.001) were more common in the second wave. Second wave patients had significantly higher respiratory rate, lower peripheral oxygen saturation, needed more supplemental oxygen and had higher incidence of pulmonary embolism. More patients received hydroxychloroquine and antibiotics during the first wave and more received steroids, antivirals and interleukin-1 antagonist during the second wave. The second wave had a shorter length of stay (14.58±7.75 vs 12.61±6.16, p<0.001) and more patients were discharged home (22% vs 10%, p<0.001).Conclusions Patients who presented during the second wave of COVID-19 pandemic appeared to be more ill clinically and based on their laboratory parameters. They required shorter hospitalisation and were more likely to be discharged home. This could represent greater expertise in handling such patients that was acquired during the first wave as well as use of more appropriate and combination therapies during the second wave.